Time to be “smart”—Opportunities Arising From Smartphone-Based Behavioral Analysis in Daily Patient Care - Akeret, Kevin; Vasella, Flavio; Geisseler, Olivia; Dannecker, Noemi; Ghosh, Arko; Brugger, Peter; Regli, Luca; Stienen, Martin N. (Frontiers in Behavioral Neuroscience, 2018)
While pathologies of the central nervous system (CNS) are often associated with neuropsychological deficits, adequate quantification and monitoring of such deficits remains challenging. Due to their complex nature, comprehensive neuropsychological evaluations are needed, which are time-consuming, resource-intensive and do not adequately account for daily or hourly fluctuations of a patient’s condition. Innovative approaches are required to improve the diagnostics and continuous monitoring of brain function, ideally in the form of a simple, objective, time-saving and inexpensive tool that overcomes the aforementioned weaknesses of conventional assessments. As smartphones are widely used and integrated in virtually every aspect of our lives, their potential regarding the acquisition of data representing an individual’s behavior and health is enormous. Alterations in a patient’s physical or mental health state may be recognized as behavioral deviation from the physiological range of the normal population, but also in comparison to the patient’s individual baseline assessment. As smartphone-based assessment allows for continuous monitoring and therefore accounts for possible fluctuations or transiently occurring abnormalities in a patient’s neurologic state, it may serve as a surveillance tool in the acute setting for early recognition of complications, or in the long-term outpatient setting to quantify rehabilitation or disease progress. This may be particularly interesting for regions of the world where healthcare resources for comprehensive clinical/neuropsychological examinations are insufficient or distances to healthcare providers are long. Here, we highlight the potential of smartphone-based behavioral monitoring in healthcare. Clinical Trial Registration: www.clinicaltrials.gov, identifier NCT03516162.